Change of Culture to Achieve Better Performance: Case at PT Sinkona Indonesia Lestari - Jatnika, Noviatni Dwi Utami; Welly, John (The Indonesian Journal of Business Administration, 2013)
PT. Sinkona Indonesia Lestari is a limited company (Ltd) or incooperation (Inc.). The share owned by two Badan Usaha Milik Negara (BUMN) and one foundation. They are: PT. (YKEP) . PT Sinkona Indonesia Lestari (SIL) have core business of quinine salts and is the only company in Indonesia who run in this business. PT. Sinkona Indonesia Lestari (SIL) corporate values are costumer focus, quality, and service. In mid-2012, majority share composition in PT. Sinkona Indonesia Lestari (SIL) owned by PT Kimia Farma. PT. Kimia Farma demand to PT. Sinkona Indonesia Lestari (SIL) to make a cultural transformation because PT. Sinkona Indonesia Lestari (SIL) can not reach performance target. By using Competing Values Framework and its instrument OCAI to diagnose type of culture that company and every division want. Competing Values Framework divided into clan culture, adhocrasy culture, marker culture, and hierarchy culture. Here the authors analyze how to implement the desired culture relate to values incompany. All analyzes and solutions use OCAI, 7S, and Total Quality Management. Based on the analysis and solutions, the PT Sinkona Indonesia Lestari preferred culture are hierarchy culture and followed by market culture. Based on the analysis, PT. Sinkona Indonesia Lestari (SIL) must do the development in the staff, skills, style, system and work in accordance with the company's existing value. Keywords: culture, corporate culture, OCAI, 7S Framework, Total Quality Management.